Influence of Product Quality, Price Perception and Advertisement Attraction to Buying Interest in Marketplace Shopee Consumers - Fitria Dwi Rahayu (Jurnal Ekonomi, 2022)
The increasing development of technology makes people use technology to meet their daily needs. With the renewal of people's shopping lifestyles, which currently tend to go through the marketplace. One of them is the Shopee marketplace, which is currently the number one platform that is widely downloaded on the Playstore and Appstore.The purpose of this research is to prove how big the significant influence of product quality (X1), price perception (X2) and advertising attractiveness (X3) variables on consumer buying interest (Y) at the Shopee marketpalce. This study uses quantitative methods using the analytical technique used is multiple linear regression. To explain the description of research related to the hypothesis by using data analysis to test the significance of the classical assumption test and test the hypothesis data collection through questionnaires. The results of the analysis of the data obtained from the t test are that the variable x1 has a coefficient value of 0.254 and a sig value of 0.024, variable x2 has a coefficient value of 0.342 and a heck value of 0.005 and a variable x3 has a coefficient value of 0.361 and a sig value of 0.002. Because the sig value has a value < of sig tolerance (0.05), the product quality, price perception and advertising attractiveness variables have a positive and significant effect on buying interest. From the results of the data obtained by the F test, it shows that all variables X have a simultaneous effect on variable Y with a value of Fcount (23.617) > Ftable (3.19) with a significance level of 0.000 < 0.05.